2020
DOI: 10.1111/mec.15600
|View full text |Cite
|
Sign up to set email alerts
|

Community assembly of bacteria and archaea in coastal waters governed by contrasting mechanisms: A seasonal perspective

Abstract: Marine planktonic bacteria and archaea commonly exhibit pronounced seasonal succession in community composition. But the existence of seasonality in their assembly processes and between-domain differences in underlying mechanism are largely unassessed. Using a high-coverage sampling strategy (including single sample for each station during four cruises in different seasons), 16S rRNA gene sequencing, and null models, we investigated seasonal patterns in the processes governing spatial turnover of bacteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 87 publications
(145 reference statements)
0
22
1
Order By: Relevance
“…By contrast, studies in the Chinese coastal bays and the East China Sea showed that stochastic processes outweighed deterministic processes in microbial community assembly [41,42]. In addition, previous research in bacterioplankton assembly also took into consideration the influence of seasonality [43,44]. These studies suggest that microbial community assembly processes are not conserved between different marine ecosystems and highlight the need for biome-specific investigations.…”
Section: Introductionmentioning
confidence: 88%
“…By contrast, studies in the Chinese coastal bays and the East China Sea showed that stochastic processes outweighed deterministic processes in microbial community assembly [41,42]. In addition, previous research in bacterioplankton assembly also took into consideration the influence of seasonality [43,44]. These studies suggest that microbial community assembly processes are not conserved between different marine ecosystems and highlight the need for biome-specific investigations.…”
Section: Introductionmentioning
confidence: 88%
“…However, in the East China Sea the relative importance of stochastic and deterministic processes varied seasonally, as deterministic processes became more influential during spring and summer (Wang et al, 2020). These studies suggest that microbial community assembly processes are not conserved between different marine ecosystems, and highlight the need for biome-specific investigations.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, the range of environmental conditions in which a species can exist (i.e. niche breadth) plays a crucial role in influencing the relative importance of stochasticity and determinism (Wu et al., 2018); and aquatic bacterial niche breadth varies seasonally (Wang et al., 2020). We thus expect that there may be seasonal variability in the community assembly of PBC and SBC.…”
Section: Introductionmentioning
confidence: 99%